A urokinase-activated recombinant diphtheria toxin targeting the granulocyte-macrophage colony-stimulating factor receptor is selectively cytotoxic to human acute myeloid leukemia blasts - Abi-Habib, Ralph J. (2004)
Novel agents to treat acute myeloid leukemia (AML) are needed with increased efficacy and specificity. We have synthesized a dual-specificity fusion toxin DTU2GMCSF composed of the catalytic and translocation domains of diphtheria toxin (DT) fused to the granulocyte-macrophage colony-stimulating factor (GM-CSF) in which the DT furin cleavage site 163RVRRSV170 is modified to a urokinase plasminogen activator (uPA) cleavage site 163GSGRSA170, termed U2. DTU2GMCSF was highly toxic to the TF1-vRaf AML cell line (proliferation inhibition assay; IC50 = 3.14 pM), and this toxicity was greatly inhibited following pretreatment with anti-uPA and anti-GM-CSF antibodies. The activity of this toxin was then tested on a larger group of 13 human AML cell lines; 5 of the 13 cell lines were sensitive to DTU2GMCSF. An additional 5 of the 13 cell lines became sensitive when exogenous pro-uPA was added. Sensitivity to DTU2GMCSF strongly correlated with the expression levels of uPA receptors (uPARs) and GM-CSF receptors (GM-CSFRs) as well as with total uPA levels. DTU2GMCSF was less toxic to normal cells expressing uPAR or GMCSFR alone, that is, human umbilical vein endothelial cells and peripheral macrophages, respectively. These results indicate that DTU2GMCSF may be a selective and potent agent for the treatment of patients with AML. (Blood. 2004;104:2143-2148)